High-Dose Hypofractionated Proton Beam Radiation Therapy Is Safe and Effective for Central and Peripheral Early-Stage Non-Small Cell Lung Cancer: Results of a 12-Year Experience at Loma Linda University Medical Center - Bush, David A.; Cheek, Gregory; Zaheer, Salman; Wallen, Jason; Mirshahidi, Hamid; Katerelos, Ari; Grove, Roger; Slater, Jerry D. (International journal of radiation oncology, biology, physics, 2013)
We update our previous reports on the use of hypofractionated proton beam radiation therapy for early-stage lung cancer patients. Eligible subjects had biopsy-proven non-small cell carcinoma of the lung and were medically inoperable or refused surgery. Clinical workup required staging of T1 or T2, N0, M0. Subjects received hypofractionated proton beam therapy to the primary tumor only. The dose delivered was sequentially escalated from 51 to 60 Gy, then to 70 Gy in 10 fractions over 2 weeks. Endpoints included toxicity, pulmonary function, overall survival (OS), disease-specific survival (DSS), and local control (LC). One hundred eleven subjects were analyzed for treatment outcomes. The patient population had the following average characteristics; age 73.2 years, tumor size 3.6 cm, and 1.33 L forced expiratory volume in 1 second. The entire group showed improved OS with increasing dose level (51, 60, and 70 Gy) with a 4-year OS of 18%, 32%, and 51%, respectively (P=.006). Peripheral T1 tumors exhibited LC of 96%, DSS of 88%, and OS of 60% at 4 years. Patients with T2 tumors showed a trend toward improved LC and survival with the 70-Gy dose level. On multivariate analysis, larger tumor size was strongly associated with increased local recurrence and decreased survival. Central versus peripheral location did not correlate with any outcome measures. Clinical radiation pneumonitis was not found to be a significant complication, and no patient required steroid therapy after treatment for radiation pneumonitis. Pulmonary function was well maintained 1 year after treatment. High-dose hypofractionated proton therapy achieves excellent outcomes for lung carcinomas that are peripherally or centrally located. The 70-Gy regimen has been adopted as standard therapy for T1 tumors at our institution. Larger T2 tumors show a trend toward improved outcomes with higher doses, suggesting that better results could be seen with intensified treatment.